2019
DOI: 10.1177/0963689719842514
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes as a Novel Structural Component in the Muscle Layers of the Goat Rumen

Abstract: Telocytes (TCs) have been identified as a distinct type of interstitial cells, but have not yet been reported in the gastrointestinal tract (GIT) of ruminants. In this study, we used transmission electron microscopy (TEM) and double-labelling immunofluorescence (IF) (antibodies: CD34, vimentin and PGP9.5) to seek TCs and investigate their potential functions in the muscle layers of the goat rumen. TCs were distributed widely in the myenteric plexus (TC-MYs) between the circular and longitudinal muscle layers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Furthermore, the occurrence of this function in the myocardium has also been proposed [1,60,61]. Previous work shows the extracellular vesicles communicating in TCs mediated by intercellular communications [4,17,61]. In the present study, it was shown that TCs have intercellular communications with nearby cells through shading/extracellular vesicles.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Furthermore, the occurrence of this function in the myocardium has also been proposed [1,60,61]. Previous work shows the extracellular vesicles communicating in TCs mediated by intercellular communications [4,17,61]. In the present study, it was shown that TCs have intercellular communications with nearby cells through shading/extracellular vesicles.…”
Section: Discussionsupporting
confidence: 73%
“…Consistently, CD34+ TCs are also reported in other mammals, amphibia and reptiles. Previous studies report CD34+ telocytes in human exocrine pancreas [13], in the rumen of goat [4], in the pancreas of Chinese salamander [19], and in the oviduct [5] and testicular parenchyma of Chinese soft-shelled turtle [45]. Using double immunofluorescence analysis in the current study, we were able to exclude the presence of CD34+/α-SMA+ myofibroblast-like telocytes.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations